Web resources management in conditions of uncertainty - Алєксєєва, Катерина Андріївна; Берко, Андрій Юліанович; Висоцька, Вікторія Анатоліївна (Technology audit and production reserves, 2015)
The main task of electronic content commerce systems (ECCS) is to facilitate the work of moderators, authors, analysts and administrators of information resources. The main goal of the ECCS functioning is to improve the functionality of information resources for users of the content. The ECCS selected topical issues range in the content set from various external sources for moderators and authors according to their ranking through the commercial content formation subsystem. An author creates a commercial content according to automatically matched information analysis from various sources of actual content. When necessary, a moderator creates new rules to filter content from different sources. He also updates other sources addresses in the subsystem of the commercial content formation. An analyst analyzes activity of target audience and the ECCS functioning. As a result, he develops new rules of statistics and dynamic analysis of the commercial content lifecycle through the commercial content support subsystem. These rules can increase the target audience range; the visits number; the unique visitors number; revisits; the visits number from search engines; the direct visits number; the regional visits number; the thematic visits number, etc. for the information resources in the ECCS. The article aims at modeling information resources processing in the ECCS. This allows us to build the general approach to design, construction and implementation of similar systems. Such solution will alternatively promote generalization and standardization of information resources processing in the ECCS methodology through the stages of commercial content formation, management and support. This helps to reduce construction time for a typical e-business systems building. Implementation of such systems allows to reduce time of production of its own commercial content, to analyze the external commercial content derived from external sources, to analyze the dynamics of the content lifecycle, to analyze the statistics of the ECCS function, to analyze the statistics of user activity of information resources in the ECCS, to increase target audience of information resources and to expand the feature set in the ECCS. The set of functional requirements and standardized specifications for creation of similar systems are the result of modeling and development of information resources processing in the ECCS. The purpose of these requirements is to provide a generalized approach to development of such ECCS as an online newspaper, an online magazine, an online publishing, distance learning system, an online shop for selling content (e-books, photos, videos, audio etc). The standardization of requirements for the ECCS construction provides creation of generalized approach for developers of such systems. This reduces time of designing and implementation of such systems and respectively helps to omit the phase of project development.